2019
DOI: 10.1002/jcc.26022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic Structure of Adjacent Carbon on the Strength of C─F⋯H─F Organofluorine Hydrogen Bonds

Abstract: We investigate the effects of the electronic structure of carbon atom on the organofluorine hydrogen bonds, C─F⋯H─F. Our results show that we can modulate the strength of organofluorine hydrogen bonds by adjusting the volume of fluorine atom in C─F via changing the electronic structure of adjacent carbon atoms. Different with the conventional hydrogen bonds, we found that instead of carbon rehybridization and hyperconjugative effects, the magnitude of fluorine atomic volume plays important roles in determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that CMC binder can be fabricated based on corn stover through an eco-friendly and economical approach. 28,122,123 For example, Hidayat et al synthesized CMC binder for lithium-ion batteries using corn cob. 28 Corn starch has been extensively studied as the binder for silicon-based anodes due to its low cost and biodegradability.…”
Section: Batteriesmentioning
confidence: 99%
“…It has been demonstrated that CMC binder can be fabricated based on corn stover through an eco-friendly and economical approach. 28,122,123 For example, Hidayat et al synthesized CMC binder for lithium-ion batteries using corn cob. 28 Corn starch has been extensively studied as the binder for silicon-based anodes due to its low cost and biodegradability.…”
Section: Batteriesmentioning
confidence: 99%